2003
DOI: 10.1074/jbc.m207970200
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Receptor-stimulating Peptide, a New Member of the Calcitonin Gene-related Peptide Family

Abstract: We isolated a novel biologically active peptide, designated calcitonin receptor-stimulating peptide (CRSP), from the acid extract of the porcine brain by monitoring cAMP production in the porcine kidney cell line LLC-PK 1 . Determination of the amino acid sequence and cDNA analysis encoding a CRSP precursor showed that this peptide has ϳ60% identity in the amino acid sequence with human calcitonin gene-related peptide type-␣ (␣CGRP), type-␤ (␤CGRP), and porcine CGRP. Northern blot analysis and radioimmunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Central administration of porcine CRSP-1 to rats suppressed food intake, increased body temperature, and decreased locomotor activity (Sawada et al 2006). Systemic administration of porcine CRSP-1 in anaesthetized rats induced no significant change in arterial pressure but did induce a significant reduction in plasma Ca (Katafuchi et al 2003a). There have been no in vivo studies of the biological actions of a CRSP-1 peptide administered to the species of origin.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Central administration of porcine CRSP-1 to rats suppressed food intake, increased body temperature, and decreased locomotor activity (Sawada et al 2006). Systemic administration of porcine CRSP-1 in anaesthetized rats induced no significant change in arterial pressure but did induce a significant reduction in plasma Ca (Katafuchi et al 2003a). There have been no in vivo studies of the biological actions of a CRSP-1 peptide administered to the species of origin.…”
Section: Introductionmentioning
confidence: 98%
“…We have recently reported isolation of a novel peptide, calcitonin (CT) receptor-stimulating peptide (CRSP-1), from porcine brain extracts by monitoring cAMP release from the kidney epithelial cell line LLC-PK 1 (Katafuchi et al 2003a). We have since identified two additional closely related peptides CRSP-2 and CRSP-3 also from porcine brain (Katafuchi et al 2003b) and have also identified homologous peptides from cattle, dogs, and horse (Katafuchi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AM2/Intermedin (AM2/IMD) can also activate CGRP1, AM1, AM2 and AMY1 receptors, albeit less potently than the cognate agonists (Ogoshi et al, 2003;Roh et al, 2004;Hay et al, 2005). CT receptor-stimulating peptide (CRSP) is another member of the family with selectivity for the CT receptor; it has not been found in humans (Katafuchi et al, 2003). BIBN4096BS is the most selective antagonist available, having a high selectivity for CGRP1 receptors, with a particular preference for those of primate origin.…”
mentioning
confidence: 99%